Nonverbal imitation skills in children with specific language delay. - Dohmen, A; Chiat, S; Roy, P (2013)
Research in children with language problems has focussed on verbal deficits, and we have less understanding of children's deficits with nonverbal sociocognitive skills which have been proposed to be important for language acquisition. This study was designed to investigate elicited nonverbal imitation in children with specific language delay (SLD). It is argued that difficulties in nonverbal imitation, which do not involve the processing of structural aspects of language, may be indicative of sociocognitive deficits. Participants were German-speaking typically developing children (n=60) and children with SLD (n=45) aged 2-3 ½ years. A novel battery of tasks measured their ability to imitate a range of nonverbal target acts that to a greater or lesser extent involve sociocognitive skills (body movements, instrumental acts on objects, pretend acts). Significant group differences were found for all body movement and pretend act tasks, but not for the instrumental act tasks. The poorer imitative performance of the SLD sample was not explained by motor or nonverbal cognitive skills. Thus, it appeared that the nature of the task affected children's imitation performance. It is argued that the ability to establish a sense of connectedness with the demonstrator was at the core of children's imitation difficulty in the SLD sample.